Fibrinolysis and the Stomach: Biochemical Identification of the “Plasmin-like” Enzyme - Thomson, J. M (Thrombosis and Haemostasis, 1974)
The ‘plasmin-like’ enzyme previously demonstrated in gastric vein blood is studied further in a series of experiments using gel filtration chromatography. By comparison with purified enzymes it is identified as plasmin. Its non-identity to trypsin is also established. The ‘plasmin-like’ activity previously demonstrated in the peripheral blood, following gastric compression at laparotomy, is also studied in a similar way and shows the same characteristics. These results confirm the view that plasmin present in the peripheral veins of these patients has been released from the stomach.